2010
DOI: 10.1371/journal.pone.0013494
|View full text |Cite
|
Sign up to set email alerts
|

Study on Differences in the Pathology, T Cell Subsets and Gene Expression in Susceptible and Non-Susceptible Hosts Infected with Schistosoma japonicum

Abstract: More than 40 kinds of mammals in China are known to be naturally infected with Schistosoma japonicum (S. japonicum); Microtus fortis (M. fortis), a species of vole, is the only mammal in which the schistosomes cannot mature or cause significant pathogenic changes. In the current study, we compared the differences in pathology by Hematoxylin-eosin staining and in changes in the T cell subsets with flow cytometry as well as gene expression using genome oligonucleotide microarrays in the lung and liver, before ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 22 publications
2
41
0
Order By: Relevance
“…Knowledge of these antigens is not just important for the immunobiology of schistosomiasis but specifically could be exploited for the discovery and development of vaccines and diagnostics. The rat has long been used as a model of immunological resistance for both S. japonicum 7 , 8 , 18 , 59 and S. mansoni 10 , 11 , 15 , 60 infection. Consequently, we screened serum and tissue antibodies from the rat using a protein microarray.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of these antigens is not just important for the immunobiology of schistosomiasis but specifically could be exploited for the discovery and development of vaccines and diagnostics. The rat has long been used as a model of immunological resistance for both S. japonicum 7 , 8 , 18 , 59 and S. mansoni 10 , 11 , 15 , 60 infection. Consequently, we screened serum and tissue antibodies from the rat using a protein microarray.…”
Section: Discussionmentioning
confidence: 99%
“…Equivalent time points were collected for the control groups in both rat time courses. Similar to previous studies, 8 , 19 , 59 , 61 we used outbred rats to better model the host heterogeneity found in schistosome‐endemic animal and human populations. Blood was collected during the time course and at necropsy.…”
Section: Methodsmentioning
confidence: 99%
“…Schistosomes from different development stages or from different susceptible hosts show differences in the level of transcription and of translation of certain genes. These differences are significantly affected by their host's environment and the host's response to the parasite infection, but knowledge regarding the mechanisms of host‐pathogen interaction via noncoding RNAs is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that M. fortis has a stronger immune response to the schistosomes during the early phases of infection, with more severe pathological lesions. Previous studies have also shown that humoral and/or cellular immunity play important roles in the restricted development of S. japonicum in M. fortis [12]. Normal sera were transferred from M. fortis into mice and the growth and development of schistosomes in these mice were affected [13].…”
Section: Introductionmentioning
confidence: 99%